About clue indicators of citations in science (Journal of Educational Sciences, 2016)
To analyze the data in scientometrics there exist several key indicators, one of which is the citation index widely used throughout the world to assess the work of researchers and research teams: scientistcitation index, journal citation index, self-citation index. Despite the ambiguous impact of numerical indicators on the science, citation indexes make it possible to compare the level of research of differentorganizations or individual researchers, have an impact on organization’s position in various rankings, often taken into account when determining the winners of various grants, contests, programs, help to identify popular topics and topics that are losing popularity. On the basis of the database Web of Science of the information company Thomson Reuters, a comparative analysis of citation index of scientists of the Republic of Kazakhstan and foreign scholars in various fields of science have been done.
Keywords: citation index; citation database; scientometrics; scientimetric indicator